The Role of Digital Technology in Increasing the Effectiveness of Health Promotion in Hospitals - Ni Made Ary Lisnawati; Ni Luh Gde Nita Sri Wahyuningsih; Ni Made Widnyani; Ni Wayan Mega Sari Apri Yani; Anik Nurhaeni (Indonesian Journal of Global Health Research, 2024)
The development of digital technology has changed many aspects of the world of health, including in the field of health promotion in hospitals. Health promotion that was previously carried out through conventional methods is now transformed using digital technology that allows for faster and more effective dissemination of information. This study aims to determine the role of digital technology in increasing the effectiveness of health promotion in hospitals. This study is a literature review that collects and analyzes various articles, journals, and studies that discuss the application of digital technology in health promotion in hospitals. The selected literature covers various types of digital technology used, such as social media, mobile applications, and hospital websites, and discusses their impact on the effectiveness of health promotion. The results of the literature review indicate that the application of digital technology in hospitals can improve the effectiveness of health promotion in various ways. Technology allows hospitals to provide timely health information, improve interaction with patients, and disseminate health messages to a wider audience. Social media and health applications, for example, can provide more personalized and easily accessible education. However, challenges such as data privacy issues, lack of access to technology in certain areas, and low digital literacy are still obstacles that need to be considered. Digital technology has great potential in improving the effectiveness of health promotion in hospitals. Despite facing some challenges, the adoption of appropriate technology can support hospitals in providing better health services and reaching more people with useful information.